DYNAMICS OF EMOTIONAL INTELLIGENCE, SELF-EFFICACY, AND PSYCHOLOGICAL EMPOWERMENT IN ENHANCING HOSPITAL HEALTHCARE WORKERS’ WORK ENGAGEMENT - Ghina Raudhatul Jannah; Fatmah Bagis; Erny Rachmawati; Alfato Yusnar Kharismasyah (ITB AAS Indonesia Surakarta, 2026)
In healthcare organizations, the emotional and psychological dynamics of the workforce are important factors that determine the quality of work engagement. This study aims to analyze the effect of emotional intelligence on work engagement by including self-efficacy and psychological empowerment as mediating variables among hospital employees in Banjarnegara Regency. This study used a quantitative approach with stratified random sampling, involving 342 respondents from three hospitals and analyzed using the Partial Least Squares Structural Equation Modeling (PLS-SEM) 3.0 method. The results showed that emotional intelligence had a positive effect on self-efficacy, psychological empowerment, and work engagement. Psychological empowerment was found to act as a mediating variable that has a direct effect on the relationship between emotional intelligence and work engagement, while self-efficacy did not show a direct effect or mediating effect. These findings confirm that psychological empowerment is a key mechanism that links the emotional abilities of healthcare workers to their work engagement. Practically, these results suggest that hospital management should prioritize strengthening emotional capacity and psychological empowerment conditions to improve employee motivation, dedication, and service quality. Further research is recommended to expand the sector context to gain a more comprehensive understanding.